Inventory of health researches (Philippine Council for Health Research and Development, 1980)
Contains 533 on-going and completed health and related studies, mostly unpublished, during the period 1992-1993. This complements the Philippine Index Medicus, which contains published researchers. Entries are arranged alphabetically by main subject; each entry contains the following elements: entry number, title, project leader, researcher(s), proponent agency, project status, duration, funding source, project cost, project site, call number, and abstract. Provides indexes on project leaders, proponent institution, title, subject and title by PCHRD priority areas. All entries may be searched thru the Health Research and Development Information Network (HERDIN), including online access. Full report of some studies may be requested from PCHRD.